Conditional knockout of REST/NRSF in excitatory neurons reduces seizure susceptibility to chemical kindling - Natali, Giulia; Michetti, Caterina; Krawczun-Rygmaczewska, Alicja; Floss, Thomas; Cesca, Fabrizia; Benfenati, Fabio (Frontiers in Cellular Neuroscience, 2023)
The Repressor Element-1 Silencing Transcription Factor/Neuron-Restrictive Silencer Factor (REST/NRSF) is an epigenetic master regulator that plays a crucial role during nervous system development and maturation. REST function was originally described during development, where it determines neuronal phenotype. However, recent studies showed that REST participates in several processes also in the adult brain, including neuronal plasticity and epileptogenesis. In this regard, the relationships between REST and epilepsy are still controversial and need further investigation. As forebrain excitatory neurons are the common final pathway of seizure susceptibility, we investigated the role of REST in epilepsy by inducing REST conditional knockout (REST-cKO) specifically in excitatory neurons of the hippocampus. To target the excitatory neuronal population, we cloned the calcium/calmodulin-dependent protein kinase IIa minimal promoter upstream of Cre recombinase. After assessing the specificity of the promoter's expression, the transgenes were packaged in an engineered adeno-associated virus able to cross the blood-brain and blood-cerebrospinal fluid barriers and delivered in the lateral ventricles of 2-month-old REST flox/flox mice to characterize, one month later, the cognitive phenotype and the seizure propensity. We show that REST-cKO mice display lower levels of anxiety in the light-dark test with respect to control mice but have unaltered motor, social and cognitive profiles. Evaluation of the susceptibility to epileptic seizures showed that REST-cKO mice are more resistant to pentylenetetrazole-induced kindling, but not to seizures induced by a single administration of the convulsant and show higher survival rates. Overall, these data suggest that the absence of REST in forebrain excitatory neurons decreases seizure susceptibility, pointing to a pro-epileptogenic role of the transcriptional repressor under conditions of pathological excitation/inhibition imbalance.